Risk factors for recurrence of vulvovaginal infections - Ekaterina V. Kolesnikova; Lyudmila K. Osipova; Alexander V. Zharov (RUDN Journal of Medicine)
Relevance. Currently, inflammatory and non-inflammatory infections of the lower urogenital tract are aserious medical problem and are one of the main reasons for seeking medical help from gynecologists. These infections account for asignificant share (from 55 to 80 %) of diseases of the reproductive system. The most common symptoms of vulvovaginal infections (VVI) are discomfort in the genitals, discharge, itching, superficial dyspareunia and unpleasant odor. In addition to the main clinical signs of inflammation, there may be the symptoms of vaginal dysbiosis that occurs without obvious signs of inflammation. Thus, VVI is manifested by awide range of clinical symptoms and is acollective term for several nosological entities. Conclusion. Despite the existence of various methods for diagnosing and treating VVI, the problem of recurrent vulvovaginal infections, which can lead to various pathological conditions both in the reproductive system and in the psychoemotional and sexual sphere of patients, remains extremely relevant and complex. These diseases require timely detection and effective treatment. Therefore, scientific research aimed at identifying the causes (risk factors) of relapse of the disease is becoming especially relevant today. However, even with the exclusion of general risk factors, the exacerbation of vaginal dysbiosis in patients is often impossible to prevent.